PERANCANGAN APLIKASI MANAJEMEN PRODUKSI KOPI PT. KARYA BAKTI BERBASIS WEB DENGAN MENGGUNAKAN MODEL PROTOTYPE - Elvira Fanisa; Sarah Kristiani Pandiangan; Okta Jaya Harmaja (Jurnal Sistem Informasi, 2024)
The coffee industry has a complex production process to the distribution of the final product. To manage this process efficiently and effectively, PT. Karya Bakti requires a reliable and easily accessible management system. Thus, this study will discuss how to design and build an information system and find out how to implement a web-based coffee production management application at PT. Karya Bakti. In this study, the UML method is used as a means of designing an object-oriented system with a Prototype model. This study produces a management information system to assist PT. Karya Bakti in processing data, both sales data, income data, roasting data, purchase or order data. so that it can increase efficiency and productivity. And this coffee production management information system is only developed specifically for PT. Karya Bakti. Even so, the author hopes that this system will be developed in a mobile version and because this information system is not yet equipped with employee management, salary, and inventory features, it is highly recommended for further research to add these features. Keywords: Design, Application, Management, Web, Prototype